The The Dynamics of General Elections in Indonesia, 1955-2019: General election - Aswino Wardhana (International Journal of Social Service and Research, 2023)
The holding of general elections is one of the means of achieving democracy and realizing a system of government that is people-sovereign and has been successfully implemented since Indonesia's independence until the current reformation period. This study aims to analyze the dynamics of general elections in Indonesia as part of the success of organizing democratic parties. The data used in this study comes from several pieces of literature relating to implementing the 1955 to 2019 general elections. The research method used is a descriptive method with a qualitative approach. With this method, the researcher attempts to describe, analyze, and explain the electoral system used during the legislative and presidential elections. The results of the study explain that Indonesia adheres to a democratic system in general elections. General elections aim to create a government of, by, and for the people. With the existing dynamics, elections in Indonesia have been successfully carried out from 1955 to 2019, both in the presidential and regional elections. The 1999 general election, which was a transition from the New Order government to reform, brought Indonesia towards a democratic political system. In 2004, the people participated directly in elections for the first time. The process of elections in Indonesia is indeed inseparable from the principles of general elections under Law Number 12 of 2003, namely direct, honest, fair, free, secret, and public.